Aflatoxin Contamination of Milk Produced in Peri-urban Farms of Pakistan: Prevalence and Contributory Factors - Yunus, Agha Waqar; Ullah, Aman; Lindahl, Johanna Frida; Anwar, Zahid; Ullah, Atta; Saif, Sharjeel; Ali, Mubarak; Zahur, Aamer Bin; Irshad, Hamid; Javaid, Shahbaz; Imtiaz, Nida; Farooq, Umer; et al. (Frontiers in Microbiology, 2020)
The present investigations were carried out to determine aflatoxin M1 contamination of milk and its contributory factors in Pakistan. In this regard, 450 dairy farms were sampled following a cross-sectional design in seven major cities of the country. Analysis of milk and feed samples using ELISA revealed high contamination of the milk with an overall average of 3164.5 ng of AFM1/L and significant differences (P < 0.001) between different cities. The milk from northern hilly areas had an average AFM1 level of 92.5 ng/L while the milk from plains had an average level of 3529.7 ng/L. In the plains, only 5.7% samples qualified the maximum tolerable limit of 500 ng of AFM1/L. Cottonseed cake with an average aflatoxin content of 600.8 µg/kg had the highest contamination level. Other feedstuffs in order of contamination level were bakery waste, waste bread, maize oil cake, pulses bran, and waste pulses. Imported oilseed cakes including palm and coconut oilcakes had an average aflatoxin level of 7.7 and 3.9 µg/kg. Wheat bran, irrespective of locality, had the lowest aflatoxin level (3.4 µg/kg) among the locally produced feedstuffs followed by different legumes (4.7-15.9 µg/kg), and crushed wheat grains (17.5 µg/kg). The average aflatoxin level in commercial dairy concentrates was 32.7 µg/kg indicating it to be a better option compared to cottonseed cake. Feed consumption and contamination data revealed that 79.7% of the total aflatoxin intake by the dairy animals was being contributed by cottonseed cake alone. On-farm storage time of oilseed cakes varied (P < 0.01) in different cities but not found to be correlated with aflatoxin contamination. In conclusion, the AFM1 levels in milk produced in peri-urban dairy farms, except for Gilgit are exceptionally high. This situation can be mitigated by reducing aflatoxin contamination in cottonseed cake and promoting use of commercial concentrates and other feedstuffs with low contamination.